Penggunaan AI dan Big Data dalam Pembelajaran Nilai-Nilai Al-Qur’an dan Hadis di Madrasah - Uzair Nazri Siregar (Yayasan Albahriah Jamiah Indonesia, 2025)
Advances in digital technology, especially in the fields of Artificial Intelligence (AI) and Big Data, have opened up new opportunities for learning innovation, including in learning the values ​​of the Qur’an and Hadith in madrasas. So far, the process of learning Islamic values ​​tends to take place conventionally and textually, so it is less responsive to the development of the times and the needs of students living in the digital era. This study aims to explore the potential and effectiveness of the use of AI and Big Data in strengthening the understanding and internalization of the values ​​of the Qur’an and Hadith in the madrasa environment. The research method used is a qualitative approach with literature studies and content analysis of several models of technology application in Islamic education. The results of the study show that AI can be used to build an adaptive learning system, personalize teaching materials according to student characteristics, and create interactive chatbots to understand the context of the hadith and verses of the Qur’an. Meanwhile, Big Data allows massive processing of learning data to analyze the effectiveness of methods, student understanding tendencies, and character strengthening. In conclusion, the integration of AI and Big Data has great potential in revitalizing the learning of the values ​​of the Qur’an and Hadith in madrasas in a more contextual, relevant, and efficient manner. Curriculum development and teacher training based on digital literacy are important prerequisites for its implementation.